Efeitos da rufiação e da manipulação do sistema genital sobre a fertilidade de éguas inseminadas - Valle, G. R. (1998)
Two trials were conducted considering 42 cycles of 29 mares and 148 cycles of 100 mares which were randomly assigned in four groups, based on a 2 × 2 factorial with unequal number of repetitions, in order to test the effects of teasing and mare's genital manipulation (thrusts) upon the AI fertility with fresh semen (Exp. 1) and transported/cooled semen at 14°C/3.6 hours (Exp. 2). On both trials, it was observed no effect of mare sexual stimulation upon fertility. On trial 2, it was observed no effect of sexual stimulation upon follicular growth dynamic and ovulation.